Diabetic macular edema (DME): dissecting pathogenesis, prognostication, diagnostic modalities along with current and futuristic therapeutic insights - Ahmed Sermed Al Sakini; Abdulrahman Khaldoon Hamid; Zainab A. Alkhuzaie; Sandra Thair Al-Aish; Shahad Al-Zubaidi; Abduljaber A’Ed Tayem; Mohammed Ayad Alobi; Anne Sermed Al Sakini; Rami Thair Al-Aish; Khayry Al-Shami; Hamdah Hanifa; Sara S. Khunda (International Journal of Retina and Vitreous)
Abstract One of the most common health concerns disturbing people within working years globally is diabetes mellitus (DM). One well-known consequence of DM is vascular damage, which can manifest as macro- and microangiopathy affecting the ocular retina. Therefore, Diabetic macular edema (DME) is a major sight-threatening complication of diabetic retinopathy (DR) worldwide. It is the most prevalent cause of significant vision impairment in diabetic patients. Long-term vision loss can be avoided by following early DME treatment guidelines in everyday life. Hence, there are various therapeutic approaches for DME management. Currently, the first-line treatment for DME is anti-VEGF family drugs, such as ranibizumab, brolucizumab, bevacizumab, and aflibercept. Nevertheless, relapses of the disease, inadequate response, and resistance during anti-VEGF therapy are still seen because of the intricate pathophysiological foundation of the disease. Consequently, there is an excellent requirement for therapeutic approaches to advance and become better at controlling diseases more satisfactorily and require fewer treatments overall. We conducted a thorough literature search in the current review to present a comprehensive overview of the primary data about the current DME therapeutic agents. We also covered the novel advances in DME management and probable future treatments being investigated and developed. This review recommended that Large clinical trials should afford sufficient evidence to support these innovative treatment modalities.